Planet gaps in the dust layer of 3D proto-planetary disks: Observability with ALMA. Issue Volume 8:Issue S299(2013) (6th January 2014) - Gonzalez, J.-F.; Pinte, C.; Maddison, S. T.; Ménard, F.
Abstract: Among the numerous known extrasolar planets, only a handful have been imaged directly so far, at large orbital radii and in rather evolved systems. The Atacama Large Millimeter/submillimeter Array (ALMA) will have the capacity to observe these wide planetary systems at a younger age, thus bringing a better understanding of the planet formation process. Here we explore the ability of ALMA to detect the gaps carved by planets on wide orbits.